HEALTH EXPLANATION FOR WASTE INTO COMPOST PROCESSING IN SMPN 1 INGIN JAYA TO REALIZE HEALTHY ADOLESCENTS AND GREEN SCHOOLS - Tahara Dilla Santi; Aulina Adamy (Universitas Muhammadiyah Aceh, 2022)
AbstractThe problem of waste does not only occur in the neighborhood but also schools. The lack of knowledge of students in sorting organic, non-organic and, B3 waste causes the waste handling process to run slowly. Whereas organic waste can be used as compost and inorganic waste can be made as handicrafts, while B3 waste must need special handling. The implementation of the service using counseling methods and waste composting training was carried out at SMPN 1 Want Jaya, Banda Aceh City. The purpose of this activity is so that students can identify, sort, and dispose of garbage in the trash cans that have been given by the striker based on the types and practice simple organic waste composting. The results of this activity are in the form of knowledge gained by students and skills acquired.Keywords: waste sorting, types of waste, composting organic waste